Cytochrome bd‐I from Escherichia coli is catalytically active in the absence of the CydH subunit. Issue 4 (21st December 2022) - Goojani, Hojjat Ghasemi; Besharati, Samira; Chauhan, Priyanka; Asseri, Amer H.; Lill, Holger; Bald, Dirk
Abstract : Cytochrome bd ‐I from Escherichia coli is a terminal oxidase in the respiratory chain that plays an important role under stress conditions. Cytochrome bd ‐I was thought to consist of the major subunits CydA and CydB plus the small CydX subunit. Recent high‐resolution structures of cytochrome bd ‐I demonstrated the presence of an additional subunit, CydH/CydY (called CydH here), the function of which is unclear. In this report, we show that in the absence of CydH, cytochrome bd ‐I is catalytically active, can sustain bacterial growth and displays haem spectra and susceptibility for haem‐binding inhibitors comparable to the wild‐type enzyme. Removal of CydH did not elicit catalase activity of cytochrome bd ‐I in our experimental system. Taken together, in the absence of the CydH subunit cytochrome bd ‐I retained key enzymatic properties. Abstract : The structure of Escherichia coli cytochrome bd is shown, with the small CydH subunit in blue. The graphs show that a CydH knock‐out strain (red) still displays cytochrome bd ‐sustained bacterial growth, similar to the wild‐type strain (blue) and a complemented strain (green).